Systematics of the Early Ordovician (late Tremadocian; Stairsian) trilobite Gonioteloides Kobayashi, with species from the Great Basin, western USA. (September 2021) - Adrain, Jonathan M.; Karim, Talia S.
Abstract: The Early Ordovician (late Tremadocian; Stairsian) trilobite Gonioteloides Kobayashi has long been known from a small number of pygidia assigned to a single formally named species, and its affinities have not been assessed. Silicified material from western Utah and southeastern Idaho includes six distinct species assigned to the genus, one of which is the type species. Two others ( G . moffitti and G . pankowskii ) are new and formally named. An additional three species that are clearly new but known from sparse material are described in open nomenclature. Gonioteloides has a stratigraphic distribution through five consecutive trilobite zones in the mid-Stairsian Stage (upper Tremadocian). Although exoskeletal morphology of three species is almost completely known, the phylogenetic affinity of the taxon remains difficult to determine. It is tentatively assigned to Dimeropygidae Hupé. UUID: http://zoobank.org/23257d6c-262b-4ef5-ae4e-cc431777e67e